Allternative methods to operational risk management - Černohorský, Jan; Teplý, Petr (Univerzita Pardubice, 2010)
In this paper we calculate capital requirement for operational risk for one of the biggest Czech banks. We have utilized two main approaches described in the literature: the Loss Distribution Approach and Extreme Value Theory, in which we have used two estimation methods - the standard maximum likelihood estimation method and the probability weighted moments (PWM). Our results proved a heavy-tailed pattern of operational risk data as documented by many researchers. Additionally, our research showed that the PWM is quite consistent when the data is limited as it was able to provide reasonable and consistent capital estimates. From a policy perspective it should be hence noted that banks from emerging markets such as the Central Europe are also able to register operational risk events and the distribution of these risk events can be estimated with a similar success than those from more mature markets.
Keywords: operational risk; economic capital; bank; extreme value theory; probability weighted method